LOS INCENTIVOS LABORALES EN EL DESEMPEÑO LABORAL DE LOS COLABORADORES DE LA EMPRESA LATINO DISTRIBUCIONES S.A.C DISTRITO DE TRUJILLO - Noriega Sánchez, Inés (2016)
This study is made in order to determine the influence of work incentives in the performance of employees of the company distributions S.A.C Latino - Trujillo 2015. The problem that was raised for this study is: how influences work incentives in the performance of employees of the company distributions S.A.C Latino? To answer this question the following hypothesis was considered: work incentives favorably influence the performance of the employees of the company Latino Distributions S.A.C. The study variables are independent variable: work incentive; dependent variable: employee performance. Descriptive research design and methods used: inductive - deductive and statistical.; and a survey as data collection technique aimed at employees from the sales and supervisor was applied. The study population consisted of 48 employees who currently work in the distributor from which it was considered work as shown with the sales that are 24 employees. In surveys applied to employees from the sales of the company Latino S.A.C distributions we can emphasize incentives if favorably influences job performance. Therefore it is concluded that the proposed program of work incentives allow the company Latino Distributions will overcome their weaknesses in the sales and better performance of its employees.